Penerapan akad hiwalah dalam praktik pada perbankan syariah - Nurhasanah, Nurhasanah; Mz, Nurse Fatimah (STAI Auliaurrasyidin Tembilahan, 2025)
This research aims to examine how the implementation of hiwalah is practiced in the contemporary era in sharia financial institutions, especially sharia banking. This research is of the type of library research or library research using qualitative methods by conducting content analysis using the Content Analysis model. The results of the research show that the conversion of classic hiwalah to contemporary hiwalah is a form of sharia banking product. The hiwalah contract can be applied to factoring, post-date checks and bill discounting. The hiwalah changes from a tabarru' character with a qard hiwalah contract to a mu'waddah using a bil ujrah hiwalah contract with the provisions of using the muthlaq hiwalah type. The bank will determine additional fees or fees for transferring customer debts based on MUI Fatwa NO:12/DSN-MUI/IV/2000 and Fatwa NO:58/DSN-MUI/V/2007. SE OJK No. 36/SEOJK.03/2015